Techniques of Slave Narrative Used by August Wilson In His Plays - Denkar, Tshering; Ahmed Bhat, Muzafar (International Journal of Psychosocial Rehabilitation, 2021)
This paper aims to focus on the importance of using the slave narrative technique by August Wilson in his plays to showcase the true emotions of the black people. We know how he uses this particular technique in all of his ten plays. This technique that Wilson uses in his plays has set him out amongst other African American writers. Wilson has used it in his plays not just to inform people but to remind the people of atrocities their ancestors have faced in the white society. His works clearly show what he wanted to achieve as a writer—not just fame but answers from the white society—and to inform his audiences about the life experiences of a black person. And how Wilson has achieved to connect with his black audiences with his stories.